Comparison of cognitive behavioral group therapy and acceptance and commitment group therapy on quality of life of breast cancer women - Sadeghi, Fatemeh; Hassani, Fariba; Emamipour, Suzan; Mirzaie, Hamidreza (International Journal of Applied Behavioral Sciences, 2017)
Background: Breast cancer diagnosis always causes a great deal of stress and result in significant changes in the patient’s routine life which is apart from physical injuries, can lead to losing social roles and increased risk of mental disorders which can negatively effects their quality of life.Objective: The present study aimed at comparing the effectiveness of cognitive-behavioral group therapy and acceptance and commitment group therapy on quality of life of breast cancer women.Methods: This is a quasi-experimental pre-test, post-test and follow-up with control group design. Thirty women suffering from breast cancer randomly and equally assigned in to two interventions and a control groups. The treatments consisted of eight weekly acceptance and commitment group therapy and also eight weekly cognitive-behavioral group therapy sessions and follow-up evaluations were carried out two months later. The QLQ-C30, QLQ-BR23 questionnaires were applied in this study.Results: Comparing with cognitive-behavioral group therapy, significant enhancement was indicated in total and all scales of QlQ-C30 and QlQ-BR23 scores in acceptance and commitment group therapy’s post-test and the results were also preserved at follow-up test.Conclusions: It is suggested by the findings of this research that acceptance and commitment program appears to be more efficient and feasible therapeutic intervention than cognitive-behavioral therapy for improving quality of life of women suffering from breast cancer.